Interactive Media on Students’ Reading Comprehension of The 8th Grade at SMPN 1 Tanah Putih Tanjung Melawan - Winda, Rahma; Nurdiana, Nurdiana; Afrizal, Afrizal (State Islamic University of Sultan Syarif Kasim Riau, 2023)
This research was conducted based on students' problems in reading comprehension, such as some students had lack of vocabulary, a view students had difficulty to find out the information according to the text they learn and the students can not comprehend the words meaning appropriately. The main focus of this study was to investigate the effect of using Interactive Media on students’ reading comprehension in recount text at 8th Grade SMPN 1 Tanah Putih Tanjung Melawan.The research design was pre-experimental with one group pre-test and post-test design. The sample of this research was eighth-grade students, totaling 30 students. Samples were taken using purposive sampling technique. In collecting data, the researcher uses a reading comprehension test to determine students' reading comprehension. In analyzing the data, the researcher used the paired sample t-test formula which was calculated using the SPSS version 28 application. The results of the data analysis showed that the significance value is lower than the significance level (0.098. < 0.05 and for effect size score was 0.77 using eta squared formula which indicated the interactive media has large effect. ). It means that Ho is rejected and Ha is accepted, So it can be concluded that there is a significant effect in students' reading comprehension before and after being taught by interactive media.